Implementation of a Simple Financial Recording and Reporting System to Enhance Congregation Trust in the Musholla's Social Funds - Jamaluddin Jamaluddin; Jamothon Gultom; Yusran Daeng Matta (Indonesian Journal of Society Engagement, 2026)
This Community Service activity was carried out at the Al-Muqorrobiin Mosque located in the Kedaung area, Pamulang, South Tangerang City. The purpose of this community service was to increase the capacity of the management team in managing social funds in a transparent and accountable manner by implementing a simple financial recording and reporting system. This community partnership program used an educational and participatory approach consisting of direct counseling, training, mentoring, and evaluation sessions that focused on conveying the importance of transparency and accountability in financial recording for the management of mosque social funds. The results showed an increase in the understanding and skills of the Al-Muqorrobiin Mosque management team regarding recording financial transactions and preparing simple and systematic financial reports; Management gained insight into the importance of financial reporting to the congregation as a means to ensure transparency in the management of social funds. The real contribution of this Community Service activity encouraged the active involvement of the Mushola management in understanding and implementing financial recording and reporting, ensuring ongoing accountability and transparency and strengthening the congregation's trust in the management of the charitable funds they have donated. Abstrak Kegiatan pengabdian Masyarakat ini dilaksanakan di Musholla Al-Muqorrobiin berlokasi di wilayah Kedaung, Pamulang, Kota Tangerang Selatan. Tujuan  pengabdian masyarakat ini  untuk meningkatkan kapasitas tim pengelola dalam mengelola dana sosial secara transparan dan akuntabel dengan menerapkan sistem pencatatan dan pelaporan keuangan yang sederhana. Program kemitraan masyarakat ini menggunakan pendekatan edukatif dan partisipatif yang terdiri dari konseling langsung, pelatihan, pendampingan, dan sesi evaluasi yang berfokus pada penyampaian pentingnya transparansi dan akuntabilitas dalam pencatatan keuangan untuk pengelolaan dana sosial masjid. Hasil menunjukkan peningkatan pemahaman dan keterampilan tim pengelola Masjid Al-Muqorrobiin terkait pencatatan transaksi keuangan dan penyusunan laporan keuangan yang sederhana dan sistematis; Pengurus memperoleh wawasan tentang pentingnya pelaporan keuangan kepada jamaah sebagai sarana untuk memastikan transparansi dalam pengelolaan dana sosial. Kontribusi nyata kegiatan Pengabdian ini mendorong keterlibatan aktif pengurus Mushola dalam memahami dan menerapkan pencatatan dan pelaporan transaksi keuangan, memastikan akuntabilitas dan transparansi yang berkelanjutan serta memperkuat kepercayaan jamaah terhadap pengelolaan dana amal yang telah mereka sumbangkan. Kata Kunci: pencatatan; pelaporan keuangan; kepercayaan jamaah dana sosial